Pengaruh Suhu, Waktu dan Ukuran Aktivasi Fisika Limbah Cangkang Kerang Darah (Anadara granosa) Terhadap Perubahan pH air Di Polman Babel - Gunawan, Herri; Subhan, Muhammad; Barmawai, Ramli; Ary Wahyudie, Ilham (Jurnal Inovasi Teknologi Terapan, 2024)
The increase in the amount of blood clam (Anadara granosa) production of 445.13 tonnes per year resulted in an increase in the potential for solid waste from their processing. This study utilizes waste from blood clams as a material for making adsorbents because the shells of these clams contain high CaCO3. The manufacture of adsorbents in this study uses physical activation intending to expand the surface in influencing the pH value of water in Polman Babel. The research method used in this research is Response Surface Methodology (RSM). The experimental design used in this research is the Box-Behnken design with 3 factors. The variables used in this study are temperature, time, and size. The temperatures used are 500℃, 600℃, and 700℃. The time used is 120 minutes, 240 minutes, and 360 minutes. The sizes used are 100 mesh, 150 mesh, and 200 mesh. The results in this study show that the optimal value of pH is found at a temperature of 345 ℃, a time of 6.4 minutes, and a size of 130.67. The resulting response of the second-order equation is convex with the optimal point at the maximum point. Based on the results of the research analysis shows that the influential independent variable is size.